Mathematical modelling of nitride layer growth of low temperature gas and plasma nitriding of AISI 316L - Triwiyanto, A. (EDP Sciences, 2014)
This paper present mathematical model which developed to predict the nitrided layer thickness (case depth) of gas nitrided and plasma nitrided austenitic stainless steel according to Fick's first law for pure iron by adapting and manipulating the Hosseini's model to fit the diffusion mechanism where nitrided structure formed by nitrided AISI 316L austenitic stainless steel. The mathematical model later tested against various actual gas nitriding and plasma nitriding experimental results with varying nitriding temperature and nitriding duration to see whether the model managed to successfully predict the nitrided layer thickness. This model predicted the coexistence of Îµ-Fe2-3N and Î³â²-Fe4N under the present nitriding process parameters. After the validation process, it is proven that the mathematical model managed to predict the nitrided layer growth of the gas nitrided and plasma nitrided of AISI 316L SS up to high degree of accuracy. Â© 2014 Owned by the authors, published by EDP Sciences.